THE CONFORMITY ASSESSMENT OF READINGMATERIALS IN ENGLISH ALIVE TEXTBOOK BASED ON SYLLABUS INDICATORS OF KTSP FOR THE ELEVENTH GRADE STUDENTS - Syarifah Fitriani and Masitowarni Siregar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
The Objective of this study was to describe clearly about the conformityAssessment of reading materials in English Alive textbook for eleventh gradestudents of Senior High School with the requirements in the school-basedcurriculum (KTSP). The research method was document analysis. The data weregathered from English Alive textbook and the syllabus of English subject for theeleventh grade students of Senior High School. After obtaining the data, theresearcher analyzed the data from the reading material contents in the textbookwith the requirements specified in the KTSP by calculating the score of the datafrom the analysis. The findings of this research state that 85.7% of text types inthe textbook meet the text types specified in the KTSP, 93,7% of the readingindicators meet the indicators specified in the KTSP,100% of generic structuresmeet the requirements specified in the KTSP. The total score for the all of aspectsin reading material are 93,2%. It shows very good as the criteria of conformitylevel. Based on the results,the reading indicators, reading text types, and featuresof reading text types (generic structures) in English Alive textbook are alreadydeveloped in accordance with the requirements specified in the School-BasedCurriculum (KTSP).